Cerasus humilis Proanthocyanidins Ameliorats Insulin Resistance through PI3K-Akt-GSK-3β Signaling Pathway in HepG2 Cells - Xinhui LIU; Yue ZHAO; Tianxu CHU; Rong ZOU; Zhe GAO; Wen ZHAO; Yancong LIU; Yasai SUN (Shipin gongye ke-ji)
Objective: The study investigated the potential targets and signaling pathways by which Cerasus humilis proanthocyanidin (CPC) regulates hepatic insulin resistance (IR) using network pharmacology. Human HepG2 cells were used to construct an insulin resistance model (IR-HepG2) to interrogate possible mechanisms. Methods: CPC targets were screened using TCMSP and Swiss Target Prediction, and key IR control points were obtained using OMIM and GeneCards. Intersections between CPC targets and key IR control points were obtained using the Venny platform. Topological, GO, and KEGG analyses of intersection targets were carried out using Cytoscape, STRING, and the biological information analysis platform. Finally, HepG2 cells co-cultured with insulin was used to establish an IR-HepG2 model and investigate glucose consumption, glucose intake, glycogen synthesis, and glycolytic enzyme activity after CPC intervention. The specific regulatory signaling pathway was confirmed to be targeted by CPC at the protein level using specific inhibitors. Results: Sixty-six key targets, including AKT1 and GSK-3β, were selected by network pharmacological analysis. Targets were mainly concentrated in regulation of kinase activity, protein phosphorylation, other GO terms, PI3K-Akt, and other KEGG signaling pathways. High-dose CPC (H-CPC) increased cellular glucose consumption by 36.02%, glucose intake by 22.03%, glycogen content by 27.99%, enhanced hexokinase (HK) activity by 18.89% and pyruvate kinase (PK) activity by 26.89%, and decreased gluconeogenic enzyme glucose-6-phosphatase (G6Pase) content by 8.77%. H-CPC up-regulated protein expression of p-PI3K/PI3K, p-Akt/Akt, and p-GSK-3β/GSK-3β (87.60%, 64.14%, and 68.31%, respectively). The PI3K inhibitor LY294002 significantly weakened CPC-mediated up-regulation of glucose consumption (29.09%) and glycogen synthesis (6.07%) in HepG2 cells via PI3K-Akt-GSK-3β. Conclusions: In this study, CPC was confirmed to ameliorate liver IR and regulate glucose metabolism disorders mainly through the PI3K-Akt-GSK-3β signaling pathway, providing a theoretical basis for the development of Cerasus humilis as a high-value producer of CPC.